Le cheval dans le transport public au XIXe siècle, à travers les collections du musée national de la Voiture et du Tourisme, Compiègne - Élise Fau (In Situ)
The horse in nineteenth-century public transport, in the collections of the national carriage and tourism museum at Compiègne. Based on a selection of the paintings, drawings and photographs held by the Compiègne museum, this paper will look at the different ways the horse was depicted in its contribution to nineteenth-century public transport. This century marked the apogee of the use of the horse, brought into question from the beginning of the twentieth century by the appearance of the motor car. Urban and inter-city public systems will be looked at in turn. Beyond a presentation of the specificities of certain horse-drawn vehicles characteristic of the period, this selection of graphic representations also throws light on society’s evolving attitudes towards these workhorses, related to the birth of a movement for the protection of animals. The pictures showing mistreatment of horses or the difficulties of their work seem to be more numerous where urban transport modes are concerned. The images of inter-city transport tens to draw more attention to the beauty and the strength of the horse teams, often shown at full gallop, rather than in some everyday position.